2019
DOI: 10.1093/sf/soy108
|View full text |Cite
|
Sign up to set email alerts
|

The Civic Footprints of Labor Market Participation: Longitudinal Evidence from the United States, 2002–2015

Abstract: While there is a widespread belief that stable employment is important for social integration, stable employment careers have become less common in America's increasingly complex labor market. Job tenure has dropped, precarious work arrangements have gained prominence, longterm unemployment has spiked, and an increasing share of the jobless are not looking for work. Against this background, we investigate the linkages between labor market experiences and volunteer activities, as indicator of people's involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…A very recent panel study is Wiertz and Lim (2019), who drew on the CPS in the 2002 to 2015 period to construct a large panel data set. Unfortunately, the study examined only the relationship between employment states and a binary variable that indicates whether or not the individual volunteers but not for how many hours.…”
Section: Ambiguous Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…A very recent panel study is Wiertz and Lim (2019), who drew on the CPS in the 2002 to 2015 period to construct a large panel data set. Unfortunately, the study examined only the relationship between employment states and a binary variable that indicates whether or not the individual volunteers but not for how many hours.…”
Section: Ambiguous Evidencementioning
confidence: 99%
“…One possible explanation for the counterintuitive results that have been obtained in previous studies is that people who work long paid work schedules are more likely to enjoy flexible working arrangements than people who work shorter schedules (Golden, 2001). This could explain why it has been observed that large increases in paid work hours positively affect the decision to start to volunteer (Wiertz & Lim, 2019) and that volunteers who work overtime contribute more hours than volunteers who work fulltime (Rotolo & Wilson, 2007).…”
Section: The Role Of the Availability Of Flexible Working Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the wake of the recession, the coupling of volunteering with incomes may be weakened because, in the wake of the recession, there may be an increase in volunteering but a decrease in earnings. Interestingly, Wiertz and Lim (2019) found that when people become unemployed, they are more likely to start volunteering and less likely to stop, thus decoupling volunteering and financial returns. Local contexts may also mitigate or exacerbate the effect of the recession on the volunteering-income correlation.…”
Section: Future Directionsmentioning
confidence: 99%
“…During unemployment, these latent functions do not get fulfilled, leading to a tremendous sense of apathy in individuals. Scholars have extended Jahoda's work to assert that rather than employment/unemployment, entry into and out of the labor force is now more critically linked to the latent functions that employment had typically provided (Wiertz & Lim 2019).…”
Section: Sense Of Selfmentioning
confidence: 99%